Raman spectra of selected mineral phases of the Morasko iron meteorite. (2nd July 2013) - Karwowski, Ł.; Helios, K.; Kryza, R.; Muszyński, A.; Drożdżewski, P.
<x xml:space="preserve">Abstract</x> Selected minerals from oval inclusions (nodules) in the Morasko IAB iron meteorite have been investigated by electron microprobe (EMP) and micro‐Raman spectroscopy. Collected spectra of quartz, forsterite‐rich olivine, chromite, kosmochlor (Na–Cr‐rich clinopyroxene) and Na‐feldspar (albite) were compared with corresponding measurements of earth minerals and used for fast identification of meteorite fragments not EMP characterized. Some structural conclusions concerning particular minerals, like solid‐state form or average crystallite size, were also drawn from the measured spectra. Copyright © 2013 John Wiley & Sons, Ltd.